Ritual and language - Kádár, Dániel Z. 1979- (Cambridge University Press, 2024)
While ritual is often associated with phenomena such as ceremonies, cursing and etiquette, it actually encompasses something much more important: it includes all instances of communally oriented language use. As such, ritual manifests itself in many forms in our daily lives, such as politeness, swearing and humour, and in many different life situations, spanning trash talk in sports events, through market bargaining, to conventional social pleasantries. This pioneering book provides an introduction to ritual language use by providing a cutting-edge, language-anchored and replicable framework applicable for the study of ritual in different datatypes and languages. The framework is illustrated with a wealth of case studies drawn from Chinese and Anglophone rituals which demonstrate how to use it effectively. The book is essential reading for both academics and students, and is relevant to pragmatics, applied linguistics and other ﬁelds